MODEL OF BANK MARKETING STRATEGY FOR INCREASED PRODUCTIVITY IN TURBULENCE OF MACROECONOMIC CONDITIONS - A CONCEPTUAL FRAMEWORK FOR BANK - Widiyanti, Shandra (Stability: Journal of Management and Business, 2024)
This research aims to develop a marketing strategy model in banks through agents, based on supporting literature studies which can then be analyzed and developed into strategic priorities.This research contributes to the novelty of the analytical framework as input to develop marketing concepts through agents in banks as a strategy to increase productivity as well as efficiency. In addition, this research is also a model for developing marketing strategies for bank products and services through agents as a new channel that has not been developed by banks in Indonesia. The conceptual framework that is the result of this study can help banks build agency programs in order to develop business strategies that focus on bank efficiency, faced with the need to increase portfolios that become sources of bank income. A framework arranged that the theories of company policies, supporting facilities and networking development can be variables to produce competent and professional agents who can support the company's achievements by increase productive agents.